Luteolin and its derivative apigenin suppress the inducible PD-L1 expression to improve anti-tumor immunity in KRAS-mutant lung cancer. (1st September 2021) - Jiang, Ze-Bo; Wang, Wen-Jun; Xu, Cong; Xie, Ya-Jia; Wang, Xuan-Run; Zhang, Yi-Zhong; Huang, Ju-Min; Huang, Min; Xie, Chun; Liu, Pei; Fan, Xing-Xing; Ma, Yu-Po; et al.
Abstract: Upregulated expression of immune checkpoint molecules correlates with exhausted phenotype and impaired function of cytotoxic T cells to evade host immunity. By disrupting the interaction of PD-L1 and PD1, immune checkpoint inhibitors can restore immune system function against cancer cells. Growing evidence have demonstrated apigenin and luteolin, which are flavonoids abundant in common fruits and vegetables, can suppress growth and induce apoptosis of multiple types of cancer cells with their potent anti-inflammatory, antioxidant and anticancer properties. In this study, the effects and underlying mechanisms of luteolin, apigenin, and anti-PD-1 antibody combined with luteolin or apigenin on the PD-L1 expression and anti-tumorigenesis in KRAS-mutant lung cancer were investigated. Luteolin and apigenin significantly inhibited lung cancer cell growth, induced cell apoptosis, and down-regulated the IFN-γ-induced PD-L1 expression by suppressing the phosphorylation of STAT3. Both luteolin and apigenin showed potent anti-cancer activities in the H358 xenograft and Lewis lung carcinoma model in vivo, and the treatment with monoclonal PD1 antibody enhanced the infiltration of T cells into tumor tissues. Apigenin exhibited anti-tumor activity in Genetically engineered KRASLA2 mice. In conclusion, both apigenin and luteolin significantly suppressed lung cancer with KRAS mutant proliferation, and down-regulated the IFN-γ induced PD-L1 expression. Treatment with the combination of PD-1 blockade and apigenin/luteolin has a synergistic effect and might be a prospective therapeutic strategy for NSCLC with KRAS-mutant. Highlights: Luteolin and apigenin can downregulate the PD-L1 expression in NSCLC with KRAS mutation. The combination of apigenin or luteolin with PD-1 mAb enhanced tumor growth control and improved survival. Apigenin but not luteolin exhibited anti-tumor activity in KRASLA2 mice.